2008
DOI: 10.1007/s10711-008-9253-1
|View full text |Cite
|
Sign up to set email alerts
|

Space filling curves and geodesic laminations

Abstract: In this paper we study a class of connected fractals that admit a space filling curve. We prove that these curves are Hölder continuous and measure preserving. To these space filling curves we associate geodesic laminations satisfying among other properties that points joined by geodesics have the same image in the fractal under the space filling curve. The laminations help us to understand the geometry of the curves. We define an expanding dynamical system on the laminations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 21 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…In Ref. [18], we show there is a transversal measure to the lamination so that the map is expanding with respect to this transversal measure.…”
Section: Geodesic Laminationmentioning
confidence: 96%
See 4 more Smart Citations
“…In Ref. [18], we show there is a transversal measure to the lamination so that the map is expanding with respect to this transversal measure.…”
Section: Geodesic Laminationmentioning
confidence: 96%
“…In Ref. [18] it is shown that the map ξ is 1/s-Hölder continuous when the IFS is self-similar, where s is the Hausdorff dimension of the attractor R. Moreover if the IFS {φ 1 , · · · , φ k } satisfies the open set condition and is self-similar then the map ξ is a measure preserving map between the Lebesgue measure of I and the normalized s-dimensional Hausdorff measure of R. If the IFS is not self-similar but s = d then ξ is measure preserving between the Lebesgue measure of I and the normalized Lebesgue measure of R ⊂ R d [18].…”
Section: Proposition 21 ([18])mentioning
confidence: 99%
See 3 more Smart Citations